Tiktok Social Media and Democracy: A Study on Generation Z in Australia Indonesia Youth Association (AIYA) Yogyakarta - Wulan Yanis Setyanti; Subkhi Ridho; Fahmi Irfanudin (Eduvest - Journal of Universal Studies, 2024)
This study examines the political awareness and perceptions of Generation Z members of the Australia-Indonesia Youth Association (AIYA) Yogyakarta through TikTok. It focuses on the phenomenon of Gen Z, often seen as politically indifferent, whose awareness is influenced by political content on TikTok. Using a qualitative approach, data were collected through in-depth interviews exploring cross-cultural political perceptions among Indonesian and Australian AIYA members. The study found that TikTok effectively serves as a platform for political campaigns, increasing political awareness among Gen Z. Members access political content, engage in discussions, and form opinions on issues like political campaigns and religious tolerance, highlighting the platform’s role in reshaping political communication in the digital era. TikTok’s algorithm tailors content to resonate with Gen Z’s digital-native traits, fostering selective and critical engagement as they seek, verify, and analyze information. Australian AIYA members view Indonesia's political campaign system as reflective of unique social and cultural dynamics. Religious tolerance, a key human rights issue, emerges as essential in assessing a country's democratic quality. Thus, Gen Z’s political awareness transcends Fear of Missing Out (FOMO), reflecting active involvement and individual responsibility in political consciousness.